KONSTRUKTIF NILAI BERITA FOTO JURNALISTIK PADA MAJALAH TEMPO EDISI 16-21 JUNI 2020 “PANGGUNG POLITIK TRAH JOKOWI” SOCIAL SEMIOTIC APPROACH - Sigit Surahman (Specta: Journal of Photography, Arts, and Media, 2020)
Constructive Value Of Photojournalism News In Tempo Magazine Issue 16-21 June 2020 "Jokowi Breed Political Stage" Social Semiotic Approach. Journalistic photography as is the case most commonly in newspapers in Indonesia. Photography has a way of spreading photos in news reporting. Social semiotics explores a variety of analytical tools for researchers interested in the potential meaning of images as well as their combination with other resources. Methods for analyzing the meaning of composition in photo media and ways of exploring text-image relationships in specific news contexts. Researchers seek to improve the position of the press photo for full partners in breaking news. This research analyzes journalistic photo strings, captions, and interesting text. The researcher also made use of a case study of the news of the nomination of Gibran Rakabuming Raka which was found in the 16-21 June 2020 edition of Malajah Tempo, "Panggung Politik Trah Jokowi". This analytical framework is further supported by examples of four photographs by press photographers. The results of the study raised the findings of a cohesive relationship between text and photos that looks constructive in conjunctive relationships, intersemiotic expansion and intersemiotic deviation between text and photos.ABSTRAKFotografi jurnalistik seperti yang terjadi paling umum pada koran di Indonesia. Fotografi memiliki cara penyebaran foto dalam pelaporan berita. Semiotik sosial menjelajah berbagai alat analisis bagi para peneliti yang tertarik pada potensi makna gambar serta kombinasi dengan sumber daya lainnya. Metode untuk menganalisis makna komposisi di media foto dan cara mengeksplorasi hubungan teks-gambar dalam spesifik konteks berita. Peneliti berupaya meningkatkan posisi foto pers untuk mitra penuh dalam menyampaikan berita. Penelitian ini menganalisis untaian foto jurnalistik, caption, dan teks yang menarik. Peneliti juga memanfaatkan studi kasus berita pencalonan Gibran Rakabuming Raka yang terdapat pada Malajah Tempo edisi 16-21 Juni 2020 “Panggung Politik Trah Jokowi”. Kerangka kerja analitis ini didukung lebih lanjut dengan contoh empat foto karya fotografer pers. Hasil penelitian memunculkan temuan hubungan kohesif antara teks dan foto terlihat konstruktif dalam hubungan konjungtif, ekspansi intersemiotik dan deviasi intersemiotik antara teks dan foto.